2009
DOI: 10.1080/19390210903070780
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic and Antioxidant Activities of Medicinal PlantStereospermum suaveolensin Streptozotocin-induced Diabetic Rats

Abstract: The ethanol extract of Stereospermum suaveolens (EESS) bark was evaluated for its antihyperglycemic in addition to antioxidant effects in streptozotocin (STZ)-induced diabetic rats by acute and subacute models at dose levels of 200 and 400 mg/kg body weight, given orally. The ethanol extract showed a significant reduction in fasting blood glucose levels when compared to the standard drug, oral Glibenclamide (0.5 mg/kg body weight). The serum of rats treated with ethanol extract showed decreased levels of serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…This observation agrees with report of Baskar et al [17] who reported antihyperglycemic activity of aqueous root extract of Rubia cordifolia in streptozotocin-induced diabetic rats. The alterations of these parameters are well known to cause anaemic condition in man [18] . Following plant extract administration, the level of RBC and its related indices were appreciably improved especially at 200 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…This observation agrees with report of Baskar et al [17] who reported antihyperglycemic activity of aqueous root extract of Rubia cordifolia in streptozotocin-induced diabetic rats. The alterations of these parameters are well known to cause anaemic condition in man [18] . Following plant extract administration, the level of RBC and its related indices were appreciably improved especially at 200 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in these haematological parameters have also been reported in humans (Balasubraimanian et al, 2009). Clinically, MCV and MCHC levels are lowered in cases of iron deficiency, sideroblastic anaemia, thalassemia and lead poisoning while they are elevated in liver diseases, megaloblastic anaemia, folic acid and vitamin B 12 deficiency (Janz et al, 2013).…”
Section: Discussionmentioning
confidence: 79%
“…This finding suggests that the ethyl acetate fraction of EESS had a potent antihyperglycemic activity in diabetic rats, which corresponded to the previous finding that the crude ethanol extract reduced blood glucose level in STZ diabetic rats. [14]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in our laboratory showed that crude ethanol extract and ethyl acetate fraction of S. suaveolens have antihyperglycemic effects in streptozotocin (STZ)-induced diabetic rats. [1415] No reports are available on the antioxidant activity of ethyl acetate fraction in the liver. Thus, the objective of the present study was to further explore our previous data by focusing now on the protective effect of S. suaveolens ethyl acetate fraction against oxidative stress in the liver of STZ-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%